Diversidade bacteriana em solos, vinhaça e semicompostagem relacionados ao cultivo de cana-de-açúcar - Omori, Wellington Pine [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Generally, industrial wastes as vinasse and filter cake cause public apprehension due to the risk of environmental impacts caused by their use as nutrients replenishment in soils with cultivation of sugarcane (Saccharum spp.). Due to lack of studies that seek to unravel the impacts of these residues in the structure and composition of bacterial communities, this work aimed to apply the 16S rRNA gene to assess the bacterial diversity present in five biomes with different sugarcane crop management besides waste vinasse and filter cake. A total of 1,090 sequences of bacterial 16S rRNA were recovered and analyzed: i) soil under sugarcane crop fertilized by vinasse (SV); ii) soil from the master channel for vinasse distribution (MC), iii) soil under native forest located next to areas of sugarcane planting (MT), iv) soil under sugarcane crop without vinasse irrigation (CH), and v) filter cake semi-composting compound (CP). Based on Richness index and rarefaction curve, the SV is considered the most diverse, followed by MT as the intermediary, and MC as the least diverse environment. The Actinobacteria phylum related to the degradation of plant biomass and production of antimicrobials has dominated the population of the CP environment, that was possibly related to high amount of lignocellulosic material available on the filter cake. CP also presented the Firmicutes and Proteobacteria phyla, both present at different stages of the composting process. Soil environments showed few taxa related to cultured bacterial genera unlike the high number of clones affiliated to bacteria not classified. Unifrac and Libshuff tests for molecular variance show that the five biomass present variation in the structure of bacterial communities. In addition, SV and MC does not share species each other. These results demonstrate that the environments containing vinasse and filter cake are different from other biomes with management of sugarcane. These ...

De maneira geral, resíduos industriais como vinhaça e torta de filtro, causam preocupação devido ao risco de impactos ambientais que podem ser causados quando utilizados na reposição de nutrientes em solos com cultivo de cana-de-açúcar (Saccharum spp.). Devido à falta de estudos que busquem desvendar os impactos destes resíduos na estrutura e composição de comunidades bacterianas, este trabalho teve como proposta utilizar o gene 16S rRNA para avaliar a diversidade bacteriana presente em 5 biomas com diferentes manejo de cana-de-açúcar e os resíduos vinhaça e torta de filtro. Foram analisados um total de 1.090 sequencias do 16S rRNA de bactérias, recuperadas de: i) solo com fertirrigação de vinhaça e plantio de cana-de-açúcar (SV), ii) solo depositado sobre o canal mestre da vinhaça (MC), iii) solo de mata nativa localizada próxima a áreas de plantio de cana-de-açúcar (MT), iv) solo com plantio de cana-de-açúcar sem a aplicação de vinhaça (CH) e v) semicomposto de torta de torta de filtro (CP). Com base na curva de rarefação e índice Richness, SV foi considerado o ambiente mais diverso, MT foi considerado como portador de diversidade intermediária e, com base nos outros índices, MC foi considerado o ambiente menos diverso. O filo Actinobacteria, relacionado com a degradação da biomassa vegetal e produção de antimicrobianos, dominou a população do ambiente CP, fato possivelmente relacionado a elevada quantidade de material lignocelulósico disponível na torta de filtro. CP também apresentou os filos Firmicutes e Proteobacteria, ambos presentes em diferentes estágios do processo de compostagem. Os ambientes de solos foram considerados como portadores de poucos táxons relacionados a gêneros bacterianos cultivados, além de apresentarem elevado número de clones afiliados a bactérias não classificadas. Os testes de variância molecular Unifrac e Libshuff demonstram que os cinco biomas ...
Keywords: Cana-de-açúcar; Biologia do solo; Genes; Resíduos; Bacterias; Soil biology